Board of directors Decision No. 72/2013 regarding regulations and controls governing factoring activity / Egyptian financial supervisory authority (EFSA); translated by The middle east library for economic services. - Egyptian financial supervisory authority (EFSA); The middle east library for economic services, translator. (2025)
Serial No. 68/2013